Perkembangan Politik Islam Kontemporer - Nursyamsu, Nursyamsu (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Palapa Nusantara Lombok NTB, 2017)
This article talks about Islam and politics are two interesting words to be discussed Islamic literatures. Many of the modern Islamic thinkers and modern neo, which tries to give an explanation of the relationship between Islam and politics.Religious and political discourse, particularly power management (religio-political power) has actually been growing since the middle of the century.In this article will discuss the contemporary Islamic thinkers view sperti Jamaluddin Al-Afghani, Rashid Rhido, al-Maududi, Hasan Al-Bana etc.Besides, in this article see the political developments in the Islamic world, including the political history of Islam in Indonesia.